Energetic Electrons Below the Inner Radiation Belt. Issue 7 (18th July 2019) - Selesnick, R. S.; Su, Yi‐Jiun; Sauvaud, J.‐A.
Abstract: Energetic electrons have occasionally been observed with high intensity in the low‐latitude quasi‐trapping region, below the inner radiation belt, where their intensity is normally low. During magnetic storms in November 2004 and July 2006, electrons reached magnetic drift shells with L <1.1. Data from the IDP electron spectrometer on the DEMETER satellite provide high energy resolution, while multiple NOAA/POES satellites provide local time coverage. After accounting for instrumental effects caused by the high intensity, electron kinetic energy is shown to reach at least 200 keV with generally softer spectra than are normally found in the stable trapping region. Electron injection from the inner belt by an enhanced convection electric field ∼5 mV/m may explain the observations. This could provide remote testing for models of global electrodynamics. Key Points: High‐intensity electrons occasionally appear below the inner radiation belt at L < 1.1 with kinetic energy up to 200 keV They may be injected from the inner belt by an enhanced convection electric field ∼5 mV/m Concurrent satellite observations provide high energy resolution and local time coverage during magnetic storms in 2004 and 2006